The remember balloons - Oliveros, Jessie; Wulfekotte, Dana (New York : Simon & Schuster Books for Young Readers, 2018)
James has a bunch of balloons, each of which holds a special memory, but as his grandfather ages and loses his own balloons, James discovers that he is gaining new ones.
Publisher's Weekly, May 2018
Kirkus Starred, July 2018
Booklist, July 2011
2.8
K-3
490L
Keywords: Memory -- Juvenile fiction; Old age -- Juvenile fiction; Families -- Juvenile fiction; Balloons -- Juvenile fiction; Memory -- Fiction; Old age -- Fiction; Family life -- Fiction; Balloons -- Fiction